Energias renováveis : a terminologia da energia solar fotovoltaica em português brasileiro e seus aspectos fraseoterminológicos - Camargo, Cristina Aparecida (2016)
Terminology constitutes a subarea of the lexical sciences presenting two different aspects: theoretical and applied. It combines the description of specialized knowledge units (SKUs) concerning a set of methodological guidelines for treating these units along with their terminographic products, such as: glossaries and dictionaries. Proposing a section of the Photovoltaic Solar Energy Dictionary (PSED) is one of the aims of this master thesis, as well as to describing, analising and inserting just one portion of the identified units, that is, the Phrase Terminologic Units (PTUs). In order to achieve it, a corpus of textual basis in Brazilian Portuguese language (BP) was organized and made up by rules, dissertations and thesis related to photovoltaic solar energy, one of the subareas of renewable energies. The explanation for choosing this subarea of knowledge was its economical and social importance to Brazil and to the world and its unsystematized terminology. With some specialists' help, four hundred and forty-eight SKUs were selected from the source corpus composed by 6.5 millions of word occurrences, which represent the related subarea. Eighty-two PTUs were recalled for analysis, aiming at investigating if the parameters known in literature, as to phraseology topic, could be identified in the introduced literature. Based in the theoretical and methodolical principles of Communicative Theory of Terminology and Socioterminology, results allow to assert that PTUs showed specific aspects which have not been undescribed yet by researchers and that, therefore, new parameters are presented as to those units, since they have a significant percentage in this study which are fundamentally important for consultants and translators.